2013
DOI: 10.1182/blood-2013-04-496893
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 mutations are frequent and represent an early event in follicular lymphoma

Abstract: Key Points• EZH2 mutations occur in more than 25% of follicular lymphoma patients.• Mutations predominantly represent an early/clonal event in the pathogenesis of the disease.Gain of function mutations in the H3K27 methyltransferase EZH2 represent a promising therapeutic target in germinal center lymphomas. In this study, we assessed the frequency and distribution of EZH2 mutations in a large cohort of patients with follicular lymphoma (FL) (n 5 366) and performed a longitudinal analysis of mutation during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
158
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(175 citation statements)
references
References 23 publications
14
158
1
2
Order By: Relevance
“…Nearly one-third of the mutations (45/159 Z 28%) detected by Fluidigm PCR and Illumina MiSeq sequencing were missed by original PCR and Sanger sequencing, albeit confirmed by further Sanger sequencing or cloning and sequencing of the PCR products. Consistent with our findings, Bodor et al 27 also found an improvement of 39% in mutation detection by amplicon-based NGS in comparison with conventional PCR and Sanger sequencing. A proportion of the somatic mutations additionally detected by Fluidigm/MiSeq sequencing may represent subclonal genetic changes.…”
Section: Detection Of Subclonal Mutationssupporting
confidence: 92%
“…Nearly one-third of the mutations (45/159 Z 28%) detected by Fluidigm PCR and Illumina MiSeq sequencing were missed by original PCR and Sanger sequencing, albeit confirmed by further Sanger sequencing or cloning and sequencing of the PCR products. Consistent with our findings, Bodor et al 27 also found an improvement of 39% in mutation detection by amplicon-based NGS in comparison with conventional PCR and Sanger sequencing. A proportion of the somatic mutations additionally detected by Fluidigm/MiSeq sequencing may represent subclonal genetic changes.…”
Section: Detection Of Subclonal Mutationssupporting
confidence: 92%
“…Because there does not appear to be a single target that can be applied to all cases, a combination of novel biomarkers (based on genomic, proteomic, transcriptomic, and metabolomic analyses of biopsies) will be required. It will be important to identify those molecular events involved in early development of the disease 90,91 and those involved in progression and transformation. 88 The prognosis and clinical course of FL appears to be highly dependent on the tumor microenvironment, and immunohistochemical methods are being assessed to address this.…”
Section: Proposed Research For the Roadmapmentioning
confidence: 99%
“…Where possible, consent should be obtained for the procurement and storage of use of excess tissue from lymph node biopsies and normal tissue at the time of presentation and at each subsequent disease relapse for research purposes in order to investigate the molecular biology of these diseases. [90][91][92] and the processes involved in transformation, should be a common goal. 88 A key issue would be performing both genetic and microenvironment analyses on longitudinal and/or paired FL biopsies to obtain an integrated view on bidirectional dependency.…”
Section: Proposed Research For the Roadmapmentioning
confidence: 99%
“…The pertinent question is whether these findings on the prognostic value of microenvironment populations and genomic alterations can be translated to application in daily clinical practice. The mutations in EZH2 are largely clustered in codon Y646 (Online Supplementary Figure S1) and are therefore technically very easily amenable to simple polymerase chain reaction (PCR) techniques, 55 while chromosomal gains can be monitored using fluorescence in situ hybridization (FISH) or NGS. 56,57 This signifies that EZH2 mutation status and chromosome 18 gain have a high potential for clinical implementation, in contrast to the microenvironment population markers CD8 and CD163.…”
Section: P-value and Fdrmentioning
confidence: 99%